Protecting Foreign Direct Investment: Implications of a WTO Regime and Policy Options - Leonardi, Renato Barros de Aguiar (Meridiano 47 - Journal of Global Studies, 2017)
Resenha do livro CORREA, Carlos M. e KUMAR, Nagesh. Protecting Foreign Direct Investment: Implications of a WTO Regime and Policy Options. Londres: Zed Books, 2003, 178 p.